FUNGSI PARTAI POLITIK DALAM PENDIDIKAN POLITIK MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2011 DAN HUKUM ISLAM - Wery Gusmansyah (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstract: The form and function of political party in various countries are different from one each in accordance with the system of politics which is applied in the country was. One of the functions of party politics is educate in education politics to the public, will be but the fact that occur at the time of this study politics are carried out by party politics are conducted only on past campaigns ahead of the election, namely the education of voters in terms of elections and the vision of the mission of the parties, regard this indicates that the education politics are conducted directed tho choose the party. In Islam party called Hizbu wich aims for is to help a muslim as an individual in carrying out is obligations to God, amar ma’ruf and forbis the evil, and to realize the leadership for the people of Islam in the entire word. From here seen clearly that, in education must exist an educator who always give instructions, guiding steer, encourage and educate humans to the goodness. And even an educator has the obligation to amar ma’ruf and forbidding evil, which became the principial importance of the main points of religion.Keywords: political education; party; politics.